Experimental and numerical investigation of axial crushing behavior of hybrid sandwich pipes - Kaman, Mete Onur; Erdem, Serkan; Albayrak, Mustafa; Gur, Mustafa; Asan, Ahmet Murat; Eroglu, Mehmet; Bozkurt, Ilyas (Sage Publications Ltd, 2026)
This study presents an experimental and numerical investigation into the axial crushing performance of hybrid sandwich pipes designed for energy absorption applications. The aim is to enhance the specific energy absorption (SEA) characteristics of crashworthy structures while maintaining low weight, which is critical in transportation and aerospace industries. Hybrid specimens were fabricated by placing carbon fiber-reinforced polymer (CFRP) pipes inside aluminum tubes to create a sandwich configuration. Axial crushing tests were conducted to assess the energy absorption behavior, and the results were compared with those of full aluminum tubes. A finite element model was developed using LS-DYNA to simulate the progressive crushing behavior and validate the experimental findings. The numerical model incorporated the Johnson-Cook and Hashin failure criteria for the aluminum and composite materials, respectively. Results demonstrate that the hybrid sandwich structure significantly improves SEA compared to conventional aluminum tubes, indicating its potential for lightweight, high-performance energy absorbers in crash scenarios.
Keywords: Axial crushing; hybrid sandwich pipe; CFRP; specific energy absorption; crashworthiness; finite element analysis; LS-DYNA